Mechanism of NLRX1 mediating JNK apoptosis pathway to participate in functional impairment of cochlear hair cells in mice with senile deafness - Yang, Xiao; Ju, Ruihua; Wang, Yaning; Gu, Lintao (Cellular and Molecular Biology, 2022)
To explore the mechanism of cochlear hair cell damage and study the prevention and treatment of sensorineural hearing loss, the effect of NLRX1 gene expression on the functional damage of cochlear hair cells in presbycusis was comprehensively analyzed. In the in vivo detection, C57BL/6 mice of different ages were used as experimental subjects. Cochlear tissues were taken after the hearing test of mice, and the number of cells and protein changes in NLRX1 immunofluorescence staining were detected. In the in vitro detection, the cochlear hair cell HEI-OE1 was used as the experimental object, and the cell proliferation activity was detected after overexpression or silencing of NLRX1.In the in vivo and in vitro experiments, the expression of JNK pathway-related proteins was simultaneously detected. The results of in vivo experiments showed that the hearing threshold of 270d -old mice was substantially greater than that of 15d-, 30d-, and 90d-old mice (P <0.05). I addition, with increasing age, the expression of p-JNK, Bcl-2, Bax, and Caspase-3 in the mouse cochlea gradually increased (P<0.05).In vitro experimental results showed that cell proliferation activity decreased after overexpression of NLRX1, and the expression of p-JNK, Bcl-2, Bax, and Caspase-3 was substantially decreased (P<0.05). Silencing NLRX1 can inhibit the above phenomenon, indicating that NLRX1 can inhibit the proliferation of hair cells in old mice through the activation of the JNK apoptosis pathway, thereby promoting the occurrence of sensorineural hearing loss.